INTED2019 Proceedings 2019
DOI: 10.21125/inted.2019.0245
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Design Students on Creativity and Social Networking Sites

Abstract: This paper investigates the perceptions about creativity and Social Networking Sites (SNS) among undergraduate design students. This is an under-researched area, and the use of phenomenography to examine this topic was deemed appropriate due to the objective of the study, which is to unpack the spectrum of views (referential aspects) and the respective causes (structural aspects) of the latter. The literature on creativity provides different perspectives on what can foster it. There is a lack of a commonly agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To that purpose, social networking sites (SNS) encourage creative interactions between students and professors. As a result, these digital strategies and efforts should ideally represent aspects of the creative processes (Souleles et al, 2019). Many researchers have evaluated a variety of digital technologies that aid in the development of new ideas and concepts, as well as the promotion of collaborative communications enabled by the use of innovative tools and enhanced learning platforms (Blair-Early, 2010;Budge, 2012;Chang & Zhu, 2011;Corso & Robinson, 2013;Hsiao et al, 2014;Idota et al, 2011;Loukis et al, 2017;Mount & Martinez, 2014;Thakur & Singh, 2012;Tillander, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To that purpose, social networking sites (SNS) encourage creative interactions between students and professors. As a result, these digital strategies and efforts should ideally represent aspects of the creative processes (Souleles et al, 2019). Many researchers have evaluated a variety of digital technologies that aid in the development of new ideas and concepts, as well as the promotion of collaborative communications enabled by the use of innovative tools and enhanced learning platforms (Blair-Early, 2010;Budge, 2012;Chang & Zhu, 2011;Corso & Robinson, 2013;Hsiao et al, 2014;Idota et al, 2011;Loukis et al, 2017;Mount & Martinez, 2014;Thakur & Singh, 2012;Tillander, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The instructional difficulties associated with fostering creativity via digital technologies are traditional instructional contexts and appropriate use of Information and Communication Technologies (ICT) for teaching and learning. The purpose of social networking sites (SNS) is to promote students' and teachers' creative interactions, and educational strategies and practices should ideally represent creative process characteristics (Souleles et al, 2019). The following is a breakdown of the paper's structure.…”
Section: Introductionmentioning
confidence: 99%
“…Late researchers have discussed the relationship between the use of SNS, students' creativity, and collaborative learning. The results described that students who actively use SNS have more opportunities to interact with other people (socialize) and/or participate in the community through collaborative learning, which in turn will affect their creativity [6]- [9], [15], [16]. Therefore, SNS can improve students' creativity directly and indirectly through collaborative learning.…”
Section: Social Networking Sites Use (Su) Student's Creativity (Sc) A...mentioning
confidence: 99%
“…In addition, previous research has also emphasized the importance use of SNS in facilitating collaborative learning that can trigger critical thinking of students [7]. This is because the elements of collaborative learning reflected the characteristics of creativity [9]. For that reason, it can also be concluded that the relationship between the use of SNS and students' creativity is indirectly influenced by the presence of collaborative learning.…”
Section: Introductionmentioning
confidence: 98%
“…Due to its transformative potential, design can play a significant role in dealing with such challenges [19]. Consequently, there is a definite and growing need to invest in pedagogies that can help learners develop skills beyond learning how to think in intellectual silos [4,13].…”
Section: Introductionmentioning
confidence: 99%